Moderasi Beragama dalam Meningkatkan Hubungan Komunikasi Masyarakat yang Efektif di Jorong Kampung Mesjid, Nagari Batahan Barat - Siti Fatimah; Kholidah Nur; Meliani Fitri; Nurjamilah Nurjamilah; Maisaroh Maisaroh; Zidan Telaumbanua; Alwanda Pratama; Putriana Nasution; Ahmad Fauzan; Pikek Rosidah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Religious moderation is an approach that emphasizes tolerance, respect for differences, and the maintenance of harmony in religious life. In the context of the Jorong Kampung Mesjid community, religious moderation plays an important role in building effective communication among its recidents. Through moderation, differances in beliefs and religious practices can be managed peacefully , preventig conflict and miscommunication. This study aims to analyze how religious moderation can enhance the effectiveness of social communication in Jorong Kampung Mesjid, through a qualitative approach carried out during service in Jorong Kampung Mesjid, the research finds that religious moderation fosters openness, emphaty, and the strengthening of values of harmony in social interactions. Proper implementation of religious moderation proves to create inclusive and harmonious spaces for dialogue, as well as enchancing solidarity within the community.